Economic (in)dependence of Arctic indigenous peoples on the example of Greenlanders - Kaczmarek, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Climate warming is causing ice in the circumpolar zones to melt, making it easier to access the natural resources there. It is not only individual states but also international corporations that are seeking to take control of these deposits. In the vast majority of cases, the indigenous inhabitants of the Arctic have little influence over the exploitation of the deposits. This is due to the economic and political superiority of the authorities of the countries they live in.
Keywords: Arctic; indigenous peoples; Greenland; Kingdom of Denmark; natural resources; international politics